A simple method for making disposable race tubes - Brian White; Dow Woodward (Fungal Genetics Reports, 1995)
Race tubes (Ryan, Beadle and Tatum 1943. Am. J. Bot. 30:784-799; Davis and de Serres 1970. 17A:79-143), glass tubes carrying strips of agar medium, are frequently used to measure the growth rates and circadian rhythmicity of Neurospora strains. However, the glass tubes can be quite difficult to fil, sterilize, and clean. The following is a simple and rapid method for using sterile disposable pipettes to make race tubes. We have had excellent results with Neurospora in these tubes.